Implementation of Discovery Learning Model on the Subject of Al-Qur'an and Hadith - Suci Prihatiningtyas; maschuriyah khurin; asiyah husna; faridl darmawan (SCHOOLAR: Social and Literature Study in Education, 2024)
This research was conducted with the aim of finding out the influence of learning motivation of class 10 students at MAN 9 Jombang before and after implementing the discovery learning learning model. The research method used is pre-experimental design with a one-group pretest-posttest design and uses a quantitative research approach. The subject of this research was class 10 IPS 2 MAN 9 Jombang. The research instruments used were pre-questionnaires and post-questionnaires as well as test results as supporting data. The questionnaire instrument is in the form of statements regarding pre-questionnaire and post-questionnaire learning motivation to measure students' learning motivation before and after implementing the discovery learning learning model which is supported by student test results. The data analysis techniques used are normality testing and hypothesis testing. Based on the calculation of the paired sample t test using IBM statistics 21 which shows that the significance value is 0.000. The pre-questionnaire significance value is 0.111>0.05 and the post-questionnaire significance value is 0.654>0.05 and it can be stated that the pre-questionnaire and post-questionnaire are normally distributed in accordance with the criteria for detecting normality using the Shapiro-Wilk test. Next, a paired sample t test was carried out, and it produced a significance value of 0.001 < an error level of 0.05, so it could be concluded that Ha was accepted. Acceptance This means that there is an influence of the problem discovery learning model on sequence and series material on students' learning motivation.